Reusable Ag@TiO2-Based Photocatalytic Nanocomposite Membranes for Solar Degradation of Contaminants of Emerging Concern - Lamine Aoudjit (MDPI AG, 2021)
Two significant limitations of using TiO2 nanoparticles for water treatment applications are reduced photocatalytic activity under visible radiation and difficulty recovering the particles after use. In this study, round-shaped Ag@TiO2 nanocomposites with a ≈21 nm diameter and a bandgap energy of 2.8 eV were synthesised by a deposition-precipitation method. These nanocomposites were immobilised into a porous poly (vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) matrix and well-distributed within the pores. The photocatalytic activity of Ag@TiO2/PVDF-HFP against metronidazole (MNZ) under solar radiation was evaluated. Further, an adaptive neuro-fuzzy inference system (ANFIS) was applied to predict the effect of four independent variables, including initial pollutant concentration, pH, light irradiation intensity, and reaction time, on the photocatalytic performance of the composite membrane on MNZ degradation. The 10% Ag@TiO2/PVDF-HFP composite membrane showed a maximum removal efficiency of 100% after 5 h under solar radiation. After three use cycles, this efficiency remained practically constant, demonstrating the membranes’ reusability and suitability for water remediation applications.